Tawhidi String Relationship (TSR) Approach to Entrepreneurial Growth in Waqf Linked Sukuk - Nasution, Lokot Zein; Siregar, Hermanto; Ismal, Rifki; Mariyanti, Tatik (Pandawan, 2025)
This paper is motivated by the still weak bargaining position of Islamic finance in the development policy constellation. In fact, Islamic finance has a variety of advantages compared to conventional, and has a variety of instruments that can be developed. One of the innovations in the development of Islamic financial instruments is the combination of sukuk and waqf or called sukuk linked waqf. The development of waqf-linked sukuk is one of the innovations and a manifestation of the importance of formulating objectives derived from religious and divine values or known as the Tawhidi String Relation (TSR). The TSR approach emphasizes the truth that comes from God, while at the same time emphasizing the importance of trying to achieve the benefit of the world. The principle of TSR is the oneness of Allah SWT which is known as Tawhid which acts as the main method for the development of Islamic finance. The oneness of Allah SWT is represented in the Al-Qur'an which is then juxtaposed with As-Sunnah. Based on the TSR approach, this paper suggests that there are many arguments or basic arguments for the importance of returning the financial sector back to the sharia economy which originates from the Al-Qur'an and As-Sunnah. This weak correlation causes the innovation results in the ecosystem for the development of waqf-linked sukuk to be weak. Therefore, it is necessary to strengthen the Islamic financial conclusion which must truly base its ecosystem on the basis of the Al-Qur'an and As-Sunnah as the foundation for the development of sukuk linked waqf.